Effectiveness of Computer-assisted Teaching Program on Malnutrition and its Prevention in Under-five Children among Adolescents Studying in Selected Pre-university College, Bengaluru - Ahmad Parry, Idreese; Shahid Sira, Syed; Arifa, Syed (International Journal of Nursing Research, 2023)
Introduction: In developing countries, malnutrition among children is a major public health issue. It is one of the most serious global risk factors for illness and death. Malnutrition during children has an impact later in life as it is associated with significant functional impairment, reduced work capacity, and decreased economic productivity. Malnourished children are more likely to suffer from delayed psychological development, poor school performance, and lower intellectual achievements. Aim: The study was aimed to evaluate the effectiveness of computer-assisted teaching program (CATP) on malnutrition and its prevention in under-five children among adolescents studying in selected Pre-university College (PUC), Bengaluru. Methods: A total of 50 students for the academic year 2014–2015 at selected PUC, Bengaluru, were enrolled through simple randomization method in this quasi-experimental study. A structured knowledge questionnaire was developed and had a total of 36 questions related to knowledge and its prevention of malnutrition. Results: After administration of teaching program, 92% of subjects had adequate knowledge and 8% had moderate knowledge. None of the subjects had inadequate level of knowledge showing effectiveness of teaching program. Post-test overall knowledge score was significantly higher in comparison to pre-test overall knowledge score (32.20 ± 8.77 vs. 8.14 ± 10.99; P = 0.01). Age, gender, nationality, family income, fathers’ occupation, mothers’ education, religion, students’ status, previous knowledge, and source of information were significantly associated with the post-test level of knowledge on malnutrition and its prevention. Conclusion: CATP is effective in increasing knowledge of adolescent regarding malnutrition and its prevention in under-five children.